2021
DOI: 10.1200/jco.21.00637
|View full text |Cite
|
Sign up to set email alerts
|

Testicular Cancer in the Cisplatin Era: Causes of Death and Mortality Rates in a Population-Based Cohort

Abstract: PURPOSE Using complete information regarding testicular cancer (TC) treatment burden, this study aimed to investigate cause-specific non-TC mortality with impact on previous treatment with platinum-based chemotherapy (PBCT) or radiotherapy (RT). METHODS Overall, 5,707 men identified by the Cancer Registry of Norway diagnosed with TC from 1980 to 2009 were included in this population-based cohort study. By linking data with the Norwegian Cause of Death Registry, standardized mortality ratios (SMRs), absolute ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
58
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 45 publications
1
58
0
2
Order By: Relevance
“…I actually do not see an oncologist anymore but I do, as I advise my patients, to continue to perform regular testicular exams and improve one’s overall health even after their formal surveillance ends, with regular visits with their primary care doctor. The crucial aspect of survivorship health maintenance was demonstrated with recent data of a study of 5707 men treated for testicular cancer showing that based on standard mortality ratios there is an overall excess non-testicular cancer-related mortality of 23% compared with the general population, especially in those patients who received radiation and/or at least two cycles of platinum-based chemotherapy, although not with those who underwent surgery alone [ 13 ]. The highest mortality was seen in those who were less than 20 years of age at diagnosis (with a 2.27-fold significantly increased risk compared to a normal population) and increasing beyond ten years of follow-up time, with the most common cause of death due to secondary malignancy with a 53% excess mortality.…”
Section: Discussionmentioning
confidence: 99%
“…I actually do not see an oncologist anymore but I do, as I advise my patients, to continue to perform regular testicular exams and improve one’s overall health even after their formal surveillance ends, with regular visits with their primary care doctor. The crucial aspect of survivorship health maintenance was demonstrated with recent data of a study of 5707 men treated for testicular cancer showing that based on standard mortality ratios there is an overall excess non-testicular cancer-related mortality of 23% compared with the general population, especially in those patients who received radiation and/or at least two cycles of platinum-based chemotherapy, although not with those who underwent surgery alone [ 13 ]. The highest mortality was seen in those who were less than 20 years of age at diagnosis (with a 2.27-fold significantly increased risk compared to a normal population) and increasing beyond ten years of follow-up time, with the most common cause of death due to secondary malignancy with a 53% excess mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Population-based studies from national registries have shown an increased risk of solid and hematological second malignant neoplasms (SMNs) in TCS post-chemotherapy. [63][64][65][66][67] The most recent National Cancer Institute study using SEER data assessed 6340 TCS initially treated with chemotherapy (1973-2014). Solid SMN risk was increased by 1.26 compared to the general population.…”
Section: Second Malignant Neoplasmsmentioning
confidence: 99%
“…The downside is that platinum agents demonstrate several critical side effects, such as nephrotoxicity and peripheral neurotoxicity, limiting the dose that might be used for patient treatment [ 22 ]. Additionally, cancer survivors previously treated with platinum disclose traceable levels of CDDP in urine and plasma many years after treatment, which is a major concern that may cause long-term side effects, triggering a decline in quality of life and, ultimately, resulting in death [ 23 , 24 , 25 ]. The current precision medicine paradigm is no longer compliant with sustaining such side effects either in a short and/or long term, and all efforts must be placed in improving risk stratification of patients with appropriate biomarkers to spare patients from futile, unnecessary treatments and their side effects.…”
Section: Introductionmentioning
confidence: 99%